Investigating the relationship between DNA methylation age acceleration and risk factors for Alzheimer's disease. Issue 1 (20th June 2018) - McCartney, Daniel L.; Stevenson, Anna J.; Walker, Rosie M.; Gibson, Jude; Morris, Stewart W.; Campbell, Archie; Murray, Alison D.; Whalley, Heather C.; Porteous, David J.; McIntosh, Andrew M.; Evans, Kathryn L.; Deary, Ian J.; et al.
Abstract: Introduction: The "epigenetic clock" is a DNA methylation–based estimate of biological age and is correlated with chronological age—the greatest risk factor for Alzheimer's disease (AD). Genetic and environmental risk factors exist for AD, several of which are potentially modifiable. In this study, we assess the relationship between the epigenetic clock and AD risk factors. Methods: Multilevel models were used to assess the relationship between age acceleration (the residual of biological age regressed onto chronological age) and AD risk factors relating to cognitive reserve, lifestyle, disease, and genetics in the Generation Scotland study (n = 5100). Results: We report significant associations between age acceleration and body mass index, total cholesterol to high‐density lipoprotein cholesterol ratios, socioeconomic status, high blood pressure, and smoking behavior (Bonferroni‐adjusted P  < .05). Discussion: Associations are present between environmental risk factors for AD and age acceleration. Measures to modify such risk factors might improve the risk profile for AD and the rate of biological ageing. Future longitudinal analyses are therefore warranted.